The European mayor - Political leaders in the changing context of local democracy - Bäck, Henry; Berg, Rikke; Sweeting, David; Johansson, Vicki; Johansson, Folke; Karlsson, David; Fallend, Franz; Reynaert, Herwig; Steyvers, Kristof; Vajdová, Zdenka; Illner, Michal; Kjaer, Ulrik; et al. (University of Gothenburg, 2007)
Major structural changes have been taking place in European local government systems around the turn of the millennium. Changes that have already had substantial consequences for local political leadership and are likely to bring about further change in the future. A number of such restructuring trends are sweeping over the continent, but from different starting points, at varying pace and in various mixed configurations. The research was designed to assess how, by playing on these different contexts, the restructuring trends and reforms inscribed in the wider framework of increasing global exchanges impact on the concept and praxis of political representation at local level. Four different trends of change are in focus: structural transformations in terms of privatisation, contracting out and general mimicry of private sector institutional arrangements ('New Public Management'); changes in central-local relations, most often in form of decentralisation, whereby new tasks have been allocated to the local level; the importance of political parties; internal institutional arrangements of local authorities. Central topics in the study are recruitment processes, perspectives on democracy, leadership styles, networks, intergovernmental relations, the importance of the party system and horizontal power relations in the local government organization.

Omfattande strukturella förändringar har skett i de europeiska kommunsystemen kring millennieskiftet. Ett antal sådana förändringar har påverkat olika länder, men från olika utgångspunkter, i olika takt och i olika konfigurationer. Forskningsprojektet syftar till att beskriva och analysera dessa institutionella och strukturella förändringars betydelse för hur politisk representation och politiskt ledarskap definieras och utformas i praxis. Fyra förändringstrender uppmärksammas: privatisering, contracting out och efterliknande av den privata sektorns institutionella arrangemang ('New Public Management'); förändringar i relationer till den centrala statsmakten, oftast i form av decentralisering som förlägger ansvaret för nya uppgifter till den lokala nivån; de politiska partiernas betydelse samt kommunernas interna institutionella arrangemang. Centrala teman i undersökningen är rekryteringsprocesser, demokratisyn, ledarstil, nätverk, stat-kommunrelationer, partisystemets betydelse samt de horisontella maktrelationerna i den kommunala organisationen.

Response rate Austria (54,8), Belgium (41,9), Czech Republic (45,1), Denmark (76,1), England (31,8), France (21,0), Germany (41,0), Greece (66,8), Hungary (59,0), Ireland (35,1), Italy (25,3), Netherlands (58,0), Poland (27,8), Portugal (22,5), Spain (24,2), Sweden (65,4), Switzerland (66,7).
The European mayor - Political leaders in the changing context of local democracy
Keywords: Working conditions; Arbetsförhållanden; Government, political systems and organisations; Regering, politiska system och organisationer; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap